Sistem Pakar Untuk Mendiagnosa Penyakit Hewan Peliharaan Menggunakan Metode Certainty Factor - Dewi Fauziah; Husni Mubarok; Neng Ika Kurniati (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
Many species of a mammal often adopt as a pet animal. Pet healthy is a factor to be considered because pets are prone to disease. Another problem is lack of veterinarian or pet clinic in Tasikmalaya region. Making an expert system to diagnose pet diseases based on its symptoms is an alternative to overcome these problems. This expert system implements certainty factor to manage uncertainty in diagnosing process and uses forward chaining as a strategy for inferring the diagnose process based on rules. One of the results of this research is a set of rules as a knowledge representation for diagnosing pet diseases; there are six rules for diagnosing rabies, parainfluenza, distemper, hepatitis, parvovirus, and coronavirus. Furthermore, the testing of calculation accurately shows that result of manual testing and software testing is the same. The certainty factor in the first trial is 0.8, and for the second one is 0.85, these mean that the certainty value is high enough to accept.